Phylogenetic Analysis of Sulawesi Endemic Butterfly Cethosia myrina Using the COI (Cytochrome Oxidase I) Gene - Iin B Mantulangi; Masrianih Masrianih; Manap Trianto; Fatmah Dhafir; Zulaikhah Dwi Jayanti; Amalia Buntu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Cethosia myrina is a butterfly species belonging to the family Nymphalidae and is endemic to Sulawesi, Indonesia. The phylogenetic relationships of this species were investigated through molecular phylogenetic analysis. Phylogenetics is a method used to examine the evolutionary relationships among living organisms. This study aimed to describe the phylogenetic relationships of C. myrina based on the mitochondrial Cytochrome Oxidase Subunit I (COI) gene. Samples were collected using an exploratory survey method. Genomic DNA was isolated using the GS 100gSYNC™ DNA Extraction Kit. DNA amplification was performed using COI primers (LCO1490 forward and HCO2198 reverse) through the Polymerase Chain Reaction (PCR) technique. Amplified DNA fragments were visualized using 1% agarose gel electrophoresis, a UV transilluminator, and a gel documentation system. Subsequent bioinformatics analyses were conducted using Gene Studio, DnaSP, BLAST, DNASTAR, and MESQUITE software. Phylogenetic reconstruction was performed using the Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods in MEGA version 11, applying the Kimura 2-parameter model with 10,000 bootstrap replicates. The results demonstrated that both the Neighbor-Joining and Maximum Likelihood methods produced phylogenetic trees that clearly illustrated the evolutionary relationships among the analyzed samples. Genetic variation analysis revealed the presence of two haplotypes, with a haplotype diversity (Hd) of 0.603 ± 0.165 and a nucleotide diversity (?) of 0.00053 ± 0.00013. Phylogenetic reconstruction formed a single monophyletic clade of C. myrina supported by a 99% bootstrap value. A genetic distance of 0.00% was observed among populations from Central Sulawesi (CMST1.1, CMST1.2, and CMST1.3), Central Sulawesi (EU275514.1), and South Sulawesi (HM998338.1), indicating an extremely close genetic relationship among these populations.